O projeto de modernidade nas crônicas da seção De Palanque de Artur Azevedo - Silva, Esequiel Gomes da [UNESP] (2014)
For this thesis we chose as corpus the chronicles subscribed by Arthur Azevedo, under the pseudonym Eloi, the hero, in Rio de Janeiro periodicals Diário de Notícias (Daily News) and Novidades (News) between the years 1885 and 1889. These chronicles were daily published in De palanque section, to which the maranhense jornalist presented a comprehensive program, promising to talk about art, culture and faits divers. As he wrote in a country that still bore some marks of its colonial past, but wanted to modernize, the chronicler was a keen observer and a scathing critic of political and social issues of the time, as can be seen in his writings, permeated by comicality. As we shall attempt to show, his dissatisfaction with this state of things led him to conceive a project of modernity carried out in that section. The penchant for laughter, revealed at an early age in São Luís, finds in the city of Rio de Janeiro, with its own problems and contrasts, the appropriate scenario for its development and is often used as a weapon to suggest changes in behavior and mindset both in those responsible for the functioning and organization of the city as in the common people, social actors that, usually listed as alibis for his criticism, were also constituted as agents of change. In addition to the physical structure of parts of the city as the Ouvidor street, the educational, political, legal and police systems, as well as practices of favor and patronage, considered scandalous by Arthur Azevedo, did not escape the mordacity of his pen. It was urgent to solve all the problems listed above since they did not fit with a modern city